Nonlinear modelling of shrinkage-induced deformations on RC retaining walls - Luís Leitão (2011)
Crack control is a main issue for design, due to its determinant role in the durability and aesthetics of concrete structures. The phenomenon of cracking can be controlled by limiting the crack width through a proper quantification and distribution of the reinforcement. However, reinforcement design methodologies proposed by RC codes to ensure crack control usually induce the adoption of large amounts of steel, quite often in excess to that really needed. Such simplified rules differ from reality due to the lack of information concerning the actual restraining effects, the nonlinear phenomena involved, as well as the explicit consideration of the imposed deformation, which takes place simultaneously with concrete relaxation. These aspects are included in the model adopted for the present paper, which is targeted for application in actual structural design of large retaining walls.